ANALYSIS OF PLANS FOR IMPLEMENTING CARBON EMISSION REDUCTION AND CREDIT EMISSION PROJECTS IN THE STEEL INDUSTRY WITH A DYNAMIC SYSTEM APPROACH CASE STUDY: PT KRAKATAU STEEL (PERSERO) - Oktioza Pratama; Zaki Almalik; Muhammad Jefta (Journal of Industrial Engineering & Management Research, 2021)
Analyze policy design for Emission Reduction Project and Carbon Emission Credits in PT. Krakatau Steel (Persero) Tbk. to reduce CO2 emission. System Dynamics model is used as basic for implementation the Emission Reduction Project scenario. Steel production, CO2 emission, and gross profit will be analyzed as macro output indicators. Moreover, feasibility study in every project will be analyzed as micro output indicator in finance point of view. This study shows that Emission Reduction Project can reduce CO2 emission. Unfortunately, the feasibility study said it is not feasible to implement although Carbon Emission Credits has been implemented too. Remembering how important the implementation of Emission Reduction Project is, it still needs another policies to support the implementation of project then. Methods: The system dynamic methodology is used in this study because it is able to model all causal relationships in the model variables by considering the feedback loop. In addition, dynamic systems are able to simulate systems for long periods of time (more than 10 years) and include policy variables and scenarios from the problem owner to intervene in the system to achieve the main goal. Result: For CO2 indicators, emission reduction project scenarios, reduction projects emissions + CDM and emission reduction projects + VCS are the best. For example, in 2029 these three scenarios produce the smallest CO2 emissions, namely 3,527,086.84 tons of CO2, compared to other scenarios, for the steel production indicator, all scenarios have the same results, so it can be said that steel production is not affected by the scenario whatever is applied. In addition, it can also be concluded that the CO2 emission reduction scenario does not affect or reduce the performance of PT. KS. For feasibility analysis, the VCS scenario is the best compared to other scenarios both in terms of Net Present Value (NPV), Internal Rate on Return (IRR) and Payback Period (PBP) for both the oxy-fuel burner project and the lime factory. However, when compared with the MARR of PT. KS (9.65%), this scenario is still not feasible (oxy-fuel burner: 7.76% and lime factory: 2.01%). so based on the results obtained, each of these policy alternatives has its own strengths and weaknesses. Determining what alternative is the best is the right of the problem owner and other stakeholders.